Dimensional characteristics of Ti-6Al-4V thin-walled parts prepared by wire-based multi-laser additive manufacturing in vacuum. Issue 5 (22nd July 2019) - Du, Farui; Zhu, Jinqian; Ding, Xueping; Zhang, Qi; Ma, Honglin; Yang, Jie; Cao, Hongzhong; Ling, Zemin; Wang, Guoyu; Duan, Xuanming; Fan, Shuqian
Abstract : Purpose: A wire-based additive manufacturing system works with high manufacturing efficiency and low dimensional precision. The purpose of this paper is to study the dimensional characteristics of Ti-6Al-4V thin-walled parts with wire-based multi-laser additive manufacturing in vacuum. Design/methodology/approach: Wire-based multi-laser additive manufacturing was carried out to understand the effect brought from different parameters. The Ti-6Al-4V thin-walled parts were formed by different height increments, power inputs and inter-layer cooling times in vacuum. Findings: The result shows that, with the number of layers increment, the layer width of thin-walled part increases gradually in the beginning and stabilizes soon afterward. Height increment, laser power and inter-layer cooling time could affect the energy input to the deposited bead and heat accumulation of thin-walled part. The layer width decreases, while the height increment increases. The increment of laser power could increase the layer width. And, the increment of inter-layer cooling time (more than 5 s) has little effect on the layer width. Originality/value: The heat dissipation mode of thin-walled parts in vacuum and the influence of different parameters on layer width are explained in this paper. It provides a reference for further understanding and controlling dimension precision of Ti-6Al-4V thin-walled part with wire-based multi-laser additive manufacturing in vacuum. At the same time, it provides a reference for researches of dimensional characteristics in the additive manufacturing industry.